Sistem Administrasi dan Keuangan Happy Bakery - Billy Indrawan; Henry Novianus Palit; Silvia Rostianingsih (Jurnal Infra, 2017)
Many jobs in Indonesia are still using manual systems in the administrative and financial system so that it is not uncommon to experience an owner of employee fraud and data loss. Therefore, a program created to keep records for all the existing administrative system.The execution of this thesis focuses on creating programs that make record is valid and easy to use even for employees as well but do granting access rights to prevent manipulation of data. In addition, this thesis aims to expand sales of Happy Bakery through a website that provides online ordering features and feature photo gallery for promotional purposes.Based on the testing that has been done, the user gives the criticism that the website has less color in the display. Website created more colored so as to attract many customers.